Abieslactone Induces Cell Cycle Arrest and Apoptosis in Human Hepatocellular Carcinomas through the Mitochondrial Pathway and the Generation of Reactive Oxygen Species - Wang, Guo-Wei; Lv, Chao; Shi, Zhi-Ran; Zeng, Ren-Tao; Dong, Xue-Yun; Zhang, Wei-Dong; Liu, Run-Hui; Shan, Lei; Shen, Yun-Heng (PLOS ONE, 2014)
Abieslactone is a triterpenoid lactone isolated from Abies plants. Previous studies have demonstrated that its derivative abiesenonic acid methyl ester possesses anti-tumor-promoting activity in vitro and in vivo. In the present study, cell viability assay demonstrated that abieslactone had selective cytotoxicity against human hepatoma cell lines. Immunostaining experiments revealed that abieslactone induced HepG2 and SMMC7721 cell apoptosis. Flow cytometry and western blot analysis showed that the apoptosis was associated with cell cycle arrest during the G1 phase, up-regulation of p53 and p21, and down-regulation of CDK2 and cyclin D1. Furthermore, our results revealed that induction of apoptosis through a mitochondrial pathway led to upregulation of Bax, down-regulation of Bcl-2, mitochondrial release of cytochrome c, reduction of mitochondrial membrane potential (MMP), and activation of caspase cascades (Casp-9 and -3). Activation of caspase cascades also resulted in the cleavage of PARP fragment. Involvement of the caspase apoptosis pathway was confirmed using caspase inhibitor Z-VAD-FMK pretreatment. Recent studies have shown that ROS is upstream of Akt signal in mitochondria-mediated hepatoma cell apoptosis. Our results showed that the accumulation of ROS was detected in HepG2 cells when treated with abieslactone, and ROS scavenger partly blocked the effects of abieslactone-induced HepG2 cell death. In addition, inactivation of total and phosphorylated Akt activities was found to be involved in abieslactone-induced HepG2 cell apoptosis. Therefore, our findings suggested that abieslactone induced G1 cell cycle arrest and caspase-dependent apoptosis via the mitochondrial pathway and the ROS/Akt pathway in HepG2 cells.